Role of therapeutic drug monitoring in pulmonary infections: use and potential for expanded use of dried blood spot samples. (March 2015) - Hofman, Susan; Bolhuis, Mathieu S; Koster, Remco A; Akkerman, Onno W; van Assen, Sander; Stove, Christophe; Alffenaar, Jan-Willem C
Respiratory tract infections are among the most common infections in men. We reviewed literature to document their pharmacological treatments, and the extent to which therapeutic drug monitoring (TDM) is needed during treatment. We subsequently examined potential use of dried blood spots as sample procedure for TDM. TDM was found to be an important component of clinical care for many (but not all) pulmonary infections. For gentamicin, linezolid, voriconazole and posaconazole dried blood spot methods and their use in TDM were already evident in literature. For glycopeptides, β-lactam antibiotics and fluoroquinolones it was determined that development of a dried blood spot (DBS) method could be useful. This review identifies specific antibiotics for which development of DBS methods could support the optimization of treatment of pulmonary infections.